Safety evaluation of the food enzyme mucorpepsin from the non‐genetically modified Rhizomucor miehei strain LP‐N836 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme mucorpepsin (EC 3.4.23.23) is produced with the non‐genetically modified Rhizomucor miehei strain LP‐N836 by Meito Sangyo Co., Ltd. The native enzyme can be chemically modified to produce a more thermolabile form. The food enzyme is free from viable cells of the production organism. It is intended to be used in the processing of dairy products for the production of cheese and fermented dairy products. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 0.108 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 95 mg TOS/kg bw per day, the mid‐dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 880. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and four matches with respiratory allergens and one with a food allergen (mustard) were found. The Panel considered that the risk of allergic reactions upon dietary exposure to this food enzyme, particularly in individuals sensitised to mustard proteins, cannot be excluded. Based on the data provided, the Panel concluded that both the native and thermolabile forms of this food enzyme do not give rise to safety concerns under the intended conditions of use.